Investigation of structure formation in lithium silicate glasses on initial stages of nucleation - Savvova, O.; Babich, O.; Kuriakin, M.; Grivtsova, A.; Topchiy, V. (Functional Materials, 2017)
Modern state of developments and applications of high-strength glass-ceramic materials based on lithium silicate glasses has been analyzed. Perspectiveness of using glass-ceramics based on lithium disilicate as transparent armor for ground vehicles has been established. Features of structure formation of lithium disilicate glasses on initial stages of nucleation have been studied. It has been established that the formation of strengthened structure containing lithium disilicate and β-spodumene in conditions of low-temperature thermal treatment will allow the use developed materials as a base in obtaining transparent glass-ceramic.